ANALISYS OF OVERPRESSURE CHARACTERISTICS IN VEN FIELD, SOUTH SUMATRA BASIN - Ammara Venty, Olifia
Ven Field is an oil and gas field in the South Sumatra Basin. The Ven Field is divided into four formations: the Gumai Formation, the Air Benakat Formation, the Muara Enim Formation, and the Kasai Formation. During drilling operations, several challenges were encountered, such as background gas and kick. The occurrence of these drilling problems may indicate the presence of overpressure zones. Poorly studied overpressure can lead to significant financial and technical losses during drilling operations. The objective of this research is to estimate pore pressure values in each drilling well using wireline log data, determine the depth of the first occurrence of overpressure in each drilling well, identify the mechanisms causing overpressure in each drilling well, and analyze the relationship between the occurrence of overpressure zones in each drilling well and tectonic and stratigraphic events in the research area. Data processing was performed on three wells using wireline log data, mud pressure data, direct pressure test data, temperature data, and drilling reports. The conditions of the research area were used as a reference to estimate pore pressure. Based on the analysis, it was found that all three wells encounter overpressure zones. The overpressure zones occur at depths ranging from 1200 to 1240 meters. The analysis indicates that the three wells have both hydrostatic pressure and overpressure conditions. The mechanism of overpressure formation is influenced by loading mechanisms with the estimated pore pressure gradient of 0.44 psi/ft to 0.83 psi/ft. The loading mechanism is caused by high sedimentation rates in the Gumai Formation due to uplift of the Barisan Mountains. The lateral drainage phenomenon occurs due to the presence of sandy layers between the claystone layers, supported by the occurrence of Intra-Gumai Formation in the research area caused by progradation events.